Reliability and validity of the persian language version of the female lower urinary tract symptoms' long form questionnaire - AbbasAli Pourmomeny; Samane Alebouye-Langeroudi; Mahtab Zargham (Wolters Kluwer Medknow Publications, 2018)
Background: Lower urinary tract symptoms (LUTS) are important and prevalent health problems that seriously affect many women and their quality of life (QOL). The female LUTS long form (FLUTS-LF) is a robust measure to assess the QOL of women. This study aimed at translating FLUTS-LF and assessing the reliability and validity of this questionnaire among Iranian patients with LUTS. Materials and Methods: Forward and backward translations of FLUTS-LF questionnaire were carried out by the research team. Data collection was conducted from November 2015 to March 2016 in Isfahan, Iran. A total of 237 women completed the Persian version of FLUTS-LF, incontinence QOL, and International Prostate Symptom Score (IPSS) questionnaires. We evaluated Cronbach's alpha coefficient, intraclass correlation coefficient (ICC), stability (reliability), and confirmatory factor analysis (CFA) of the questionnaire. Results: The mean (standard deviation) age of the participants was 45.4 (12.50) years (range 20-70 years). Face and content validities were acceptable and missing data comprise 2% of the total data. Internal consistency (Cronbach's alpha) of the urinary symptoms was 0.78. ICC of the total score in urinary symptoms section was 0.95. Indexes of factor analysis were assessed and found to be acceptable. A high correlation was observed between the total scores of FLUTS-LF and IPSS. Conclusions: It seems that FLUTS-LF questionnaire can be a suitable instrument for assessing LUTS and their impacts on Iranian women's QOL.